Inter-relationship of intelligence-quotient and self-concept with dental caries amongst socially handicapped orphan children - PKS Virk; R L Jain; A Pathak; U Sharma; J S Rajput (Wolters Kluwer Medknow Publications, 2012)
Context : India has been the focus of many health surveys among normal, physically, and mentally handicapped children. However, the data, concerning oral health conditions of socially handicapped children living in orphanages, are scanty. Aims: To study the effect of parental inadequacy, environmental deprivation, and emotional disturbances on dental caries through intelligence quotient (IQ) and self-concept in orphan children and also to co-relate dental caries with different levels of IQ and self-concept. Settings and Design: The study was carried out amongst socially handicapped children living in orphanages. Patients and Methods: 100 children in the age group of 10-14 years from orphanages were selected. Malin's Intelligence Scale for Indian Children (MISIC) was used to assess the intelligence quotient; self-concept questionnaire to assess self-concept of the child and recording of dental caries status of children was done as per WHO Index (1997). StatisticaL Analysis Used : To assess the relationship of dental caries with IQ, student's unpaired t-test was used and; to find the relationship between self-concept and dental caries, Karl-Pearson's coefficient of co-relation was applied. Results: the children in orphanages had a lower IQ and high caries experience but had an above average self-concept. There was also no co-relation between dental caries and self-concept. Conclusions: Orphan children, being socially handicapped, are at an increased risk for dental caries due to a lower IQ level, parental deprivation, and institutionalization. Moreover, lack of co-relation between dental caries and self-concept could be explained by the fact that dental caries is a lifelong process whereas different dimensions of self-concept are in a state of constant flux.